Evaluation of Electronic Evidence in Criminal Justice in the Era of Advanced Artificial Intelligence Technology - Benny Sumardiana; Pujiyono Pujiyono; Irma Cahyaningtyas; Cahya Wulandari (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
Law enforcement is one of the many facets of society that have seen substantial changes as a result of the quick growth of digital technology, especially artificial intelligence (AI). The purpose of this study is to assess how electronic evidence is used in Indonesia's criminal justice system, pinpoint the difficulties encountered, and offer suggestions for enhancing the efficiency and equity of electronic evidence in the age of artificial intelligence. In line with the technological elements included in digital and criminal investigation research methodologies, this qualitative study aids in the creation of a theoretical framework for the use of electronic evidence in the setting of artificial intelligence. The results show that Indonesian law is now able to meet the needs of the digital age with its adaptation to technological advancements. Finding material truth in court proceedings is made possible by electronic evidence, which is legally acknowledged as a legitimate tool in criminal justice. To successfully address these issues and optimize the use of AI in the legal system, it is imperative to develop a strong ethical framework, improve law enforcement capacities, and update rules on a regular basis.